2022
DOI: 10.3389/fmolb.2022.836862
|View full text |Cite
|
Sign up to set email alerts
|

Exploring New Characteristics: Using Deep Learning and 3D Reconstruction to Compare the Original COVID-19 and Its Delta Variant Based on Chest CT

Abstract: Purpose: Computer-aided diagnostic methods were used to compare the characteristics of the Original COVID-19 and its Delta Variant.Methods: This was a retrospective study. A deep learning segmentation model was applied to segment lungs and infections in CT. Three-dimensional (3D) reconstruction was used to create 3D models of the patient’s lungs and infections. A stereoscopic segmentation method was proposed, which can subdivide the 3D lung into five lobes and 18 segments. An expert-based CT scoring system was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…However, patients with the Delta variant showed higher neurological symptoms ( 21 ). A recent retrospective research of 107 patients revealed that the peak of pneumonia occurred later in the Delta variant than those with the Original COVID-19 ( 22 ), whereas our data on chest CT scans were collected upon admission. Notably, patients infected with the Delta variant had a significantly prolonged virus shedding time, which could lead to persistent medical deterioration.…”
Section: Discussionmentioning
confidence: 99%
“…However, patients with the Delta variant showed higher neurological symptoms ( 21 ). A recent retrospective research of 107 patients revealed that the peak of pneumonia occurred later in the Delta variant than those with the Original COVID-19 ( 22 ), whereas our data on chest CT scans were collected upon admission. Notably, patients infected with the Delta variant had a significantly prolonged virus shedding time, which could lead to persistent medical deterioration.…”
Section: Discussionmentioning
confidence: 99%
“…Their initial goal was generally to save radiologists' time in reviewing medical images and to improve the accuracy of lesions identification. With computer-aided diagnosis methods, physicians can accurately obtain inflammation annotation in CT slices and accurately calculate the percentage of inflammation (POI) and its inflammatory density for each lung lobe or lung segment in a short time ( 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…The major pathogen of COVID-19 has been identified as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), yet new variants kept appearing, leading to ongoing worldwide outbreaks of COVID-19 at different magnitudes. SARS-CoV-2 Delta variant (also known as lineage B.1.617.2), a variant of concern identified by the World Health Organization (WHO), became the primary strain of the COVID-19 pandemic in 2021 ( 2 ), affecting more than 75% of countries worldwide. In March 2022, a new variant named Deltacron with Delta variant as the main stem was confirmed to exist by WHO, which will exacerbate the plague of COVID-19 to humans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation